2.04.008: Black and White photograph by Shane Kelly: Don and Des Walsh "The Last Call, Bridgett's Pub, Feb 19, 1994" (2 copies) - Shane Kelly Photo (1994)
2.04.008 Don Walsh and Des Walsh at Bridgetts's Last Call closing night. A sad night for musicians in the city. Bridgetts was always a great pub for music, for both listening and for somewhere to get a gig. The second copy has not been digitized.